Comparative analysis of the nutritional and biological properties between the pileus and stipe of Morchella sextelata - Qiu, Zhiheng; Ren, Shuhua; Zhao, Jiazhi; Cui, Lingxiu; Li, Hongpeng; Jiang, Bei; Zhang, Miao; Shu, Lili; Li, Tianlai (Frontiers in Nutrition, 2024)
Morchella sextelata is a highly prized edible mushroom and is widely consumed for its distinctive taste and texture. The stipe of M. sextelata is significantly lower in priced compared to the pileus.The aim of this study was to conduct a comprehensive comparative analysis of the nutritional and biological properties between the pileus and stipe of M. sextelata. The results revealed that the stipe exhibited comparable levels of various nutrients and bioactive compounds to those found in the pileus. The stipe showed significantly higher levels of crude dietary fiber, various mineral elements, vitamins, amino acids, 5′-nucleotides, fatty acids, and specific sugars. Additionally, it also demonstrated significant abundance in bioactive compounds such as total flavonoids and ergothioneine. Overall, our study provides valuable insights into unlocking further knowledge about M. sextelata's nutritional composition while highlighting its potential health benefits associated with different parts of this highly esteemed edible mushroom.